Plyometrics, power and football (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2025)
Introduction: Currently, physical preparation in football must be developed based on factors that contribute to improving sports performance. This requires the application of specific methods to enhance the physical capacities essential for team performance. Objective: Conduct a bibliographic review to provide a foundation on the effects of plyometric training on the development of lower limb power in football players. Justification: This review highlights research on the effects of plyometric training on lower limb power, offering effective tools for football coaches to optimize training methods. Methodology: A bibliographic review was conducted, considering recent studies aimed at determining the relevance of plyometric training in enhancing lower limb power in football players. Additionally, the most effective methods for assessing lower limb power were identified. The findings of each study were analyzed to extract key information for this article. Results: Findings were obtained through statistical analyses from each study, identifying the effects of the independent variable on the dependent variable, as well as the factors influencing these effects. Conclusions: There is substantial evidence regarding the effects of plyometric training on lower limb power in football players, emphasizing the importance of proper planning to foster athlete development.
Keywords: Plyometrics; lower limb power; football